2017
DOI: 10.1371/journal.pone.0169100
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10/IP-10 Neutralization Can Ameliorate Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome in Rats

Abstract: The role of C-X-C motif chemokine 10 (CXCL10), a pro-inflammatory factor, in the development of acute respiratory distress syndrome (ARDS) remains unclear. In this study, we explored the role of CXCL10 and the effect of CXCL10 neutralization in lipopolysaccharide (LPS)-induced ARDS in rats. The expression of CXCL10 and its receptor chemokine receptor 3(CXCR3) increased after LPS induction. Moreover, neutralization of CXCL10 ameliorated the severity of ARDS by reducing pulmonary edema, inhibiting the release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 46 publications
2
53
2
Order By: Relevance
“…Based on the results obtained in our study, the ALI group presented with lower levels of PaO 2 , while the PaCO 2 , numbers of total cellular score, WBC number, LPI, and the W/D weight ratio had evidently increased when comparing them with the control group. According to previous reports, the recruitment of leukocytes and neutrophil‐mediated lung injury has been reported to play essential roles in the development of ARDS . ARDS, primarily known to be the severe complication of ALI, had been characterized by the accumulation of protein‐rich fluid inside the alveoli, occurring as a result of an increased pulmonary capillary permeability .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results obtained in our study, the ALI group presented with lower levels of PaO 2 , while the PaCO 2 , numbers of total cellular score, WBC number, LPI, and the W/D weight ratio had evidently increased when comparing them with the control group. According to previous reports, the recruitment of leukocytes and neutrophil‐mediated lung injury has been reported to play essential roles in the development of ARDS . ARDS, primarily known to be the severe complication of ALI, had been characterized by the accumulation of protein‐rich fluid inside the alveoli, occurring as a result of an increased pulmonary capillary permeability .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the recruitment of leukocytes and neutrophil-mediated lung injury has been reported to play essential roles in the development of ARDS. 21 ARDS, primarily known to be the severe complication of ALI, had been characterized by the accumulation of protein-rich fluid inside the alveoli, occurring as a result of an increased pulmonary capillary permeability. 22 An increase in the W/D ratio and LPI are two important mechanisms that lead directly to an increase in ARDS inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was flipped in the 72-h infection group, with ST2 KO mice showing significantly higher KC levels than WT mice. IP-10 is a sensitive marker of active rhinovirus infection (27) and has also been shown to contribute to recruitment of various types of leukocytes, such as neutrophils (28). After 16 and 72 h of HRV1B infection, WT and KO mice had increased IP-10 levels in BAL fluid (Fig.…”
Section: St2 In Airway Infection and Inflammationmentioning
confidence: 95%
“…Overall, 35/42 (83.3%) participants who received BMS-986184 in the SAD study and 8/12 (66.7%) participants who received BMS-986184 in the MAD study completed the study period. The main reasons for not (4,4) 0.492 18.6 0.313-0.671 ω 2 K a (5,5) 0.181 58.2 0-0.387 ω 2 K in (6,6) 0.117 30.1 0.048-0.186 ω 2 K deg (7,7) 0.031 354.3 0-0.249 ω 2 K int (8,8) 0.034 120.3 0-0.115 ω 2 K SS (9,9) 3.181 58.0 0-6.794 ω 2 F1 (10,10) 0.260 139.6 0-0.97 ω 2 E M AX (11,11) 0.347 170. completing the study were withdrawal of consent (3/54; 5.6%) and adverse events (AEs; 3/54; 5.6%). Baseline characteristics for both the SAD and MAD cohorts are shown in Table 1.…”
Section: Study Populationmentioning
confidence: 99%
“…Interferon (IFN)-γ -induced protein 10 (IP-10/CXC motif chemokine [CXCL]10), a member of the CXC chemokine family, is involved in a diverse range of human diseases, including inflammatory and autoimmune diseases (eg, rheumatoid arthritis, 1 systemic lupus erythematosus, 2 and type 1 diabetes mellitus 3 ) and cancer. [4][5][6] IP-10 is secreted by immune cells (lymphocytes, 7 eosinophils, 8 and monocytes 9 ) and nonimmune cells (hepatocytes, 7 endothelial cells, 9 fibroblasts, 9 stromal cells, 10 and keratinocytes 9 ) in response to inflammatory stimuli, 6,11 and its production is significantly increased in the circulation and diseased tissues of patients with several autoimmune diseases. 12,13 Experimental models of ulcerative colitis (UC) have demonstrated that IP-10 mediates the trafficking of immune cells from the circulation to the in-flamed colon 14 and regulates crypt cell proliferation.…”
mentioning
confidence: 99%